Pengaruh Implementasi Sistem Manajemen Mutu ISO 9001:2008 Dan Kemampuan Mengajar Widyaiswara Terhadap Kompetensi Lulusan Diklat - Dewi Setiawati (Jurnal Konseling dan Pendidikan, 2016)
This research mainly aims to explore competencies of training graduated which focuses on factors that influence competencies of training graduates, such as the implementation of quality management system ISO 9001:2008 and teaching quality of Widyaiswara. The main research problem addressed in this study is how the implementation of quality management system ISO 9001:2008 and teaching quality of Widyaiswara contribute to competencies of training graduates, both partially and altogether.I conducting this research, explanatory survey method is used with questionairres using likert and interval scales as the data collection techniques, that are distributed to 51 graduates of training at PPPPTK Penjas dan BK. To analyse the data, the study employs PPM (Pearson Product Moment), to investigate the direct and non-direct correlations of dependent and independent variables. Significance tests are administered using F-test and t-test. The results show that (1) the impelementation of quality management system ISO 9001:2008 significantly influences competencies of training graduates; (2) teaching quality of Widyaiswara significantly influences competencies of training graduates; and (3) both the implementation of quality management system ISO 9001:2008 and teaching quality of Widyaiswara significantly influence competencies of training graduates.